2019
DOI: 10.3389/fimmu.2019.00776
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functions of Bombyx mori Peptidoglycan Recognition Protein 2 in Immune Responses to Bacteria and Viruses

Abstract: Peptidoglycan recognition protein (PGRP) is an important pattern recognition receptor in innate immunity that is vital for bacterial recognition and defense in insects. Few studies report the role of PGRP in viral infection. Here we cloned two forms of PGRP from the model lepidopteran Bombyx mori : BmPGRP2-1 is a transmembrane protein, whereas BmPGRP2-2 is an intracellular protein. BmPGRP2-1 bound to diaminopimelic acid (DAP)-type peptidoglycan (PGN) to activate the canonical immune defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 74 publications
0
39
0
Order By: Relevance
“…Innate immune signaling pathways and resistance-related genes play an important role in antiviral defense. The Imd and Toll signaling pathways participate in the antiviral immune response ( 36 , 54 ) but do not seem to play roles in the silkworm BmNPV response. BmNPV infection induces cGAMP production in BmE cells and BmSTING responds to the cGAMP and activated Dredd caspase-mediated NF-κB antiviral signaling pathways ( 69 ).…”
Section: Silkworm Immune Response To Baculovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune signaling pathways and resistance-related genes play an important role in antiviral defense. The Imd and Toll signaling pathways participate in the antiviral immune response ( 36 , 54 ) but do not seem to play roles in the silkworm BmNPV response. BmNPV infection induces cGAMP production in BmE cells and BmSTING responds to the cGAMP and activated Dredd caspase-mediated NF-κB antiviral signaling pathways ( 69 ).…”
Section: Silkworm Immune Response To Baculovirusmentioning
confidence: 99%
“…Additionally, Apsup from LdMNPV inhibits apoptosis by preventing proteolytic Dronc (IC) processing ( 87 ). Recently, our research demonstrated that peptidoglycan recognition protein (PGRP) is regulated by virus to inhibit host antiviral apoptosis, which is well known to recognize invading bacteria and fungi to activate host immune defenses ( 54 ). For example, BmNPV induces BmPGRP2-2 to suppress PTEN and the inhibition of PI3K/Akt signaling, increase p-Akt production and activation, and inhibit cell apoptosis ( 54 ).…”
Section: Viral Immune Evasion Mechanismmentioning
confidence: 99%
“…Unfortunately, there is currently no evidence that any of the above-mentioned PRRs are involved in insect virus recognition, with the exception of the nucleic acid sensor Dicer-2 that can act as a PRR of double-stranded RNA in parallel to the RNAi pathway ( 107 ). Recently, B. mori cGAMP and PGRP2 were confirmed to be involved in host responses to BmNPV ( 93 , 109 ). In Drosophila , Toll, IMD and JAK/STAT pathway may be involved in antiviral immunity ( 4 , 65 , 110 ).…”
Section: The Program Of Avp Synthesis and Its Mechanism Of Action In mentioning
confidence: 99%
“…For example, baculovirus induces Bmserpin2 to inhibit the melanization reaction mediated by the PPO pathway, which also induces BmPGRP2-2 to suppress PTEN, resulting in increased p-Akt that can inhibit cell apoptosis and autophagy. Meanwhile, silkworm viruses usurp the ERK pathway by downregulating BmSpry (57)(58)(59)(60). It is noteworthy that targeting these hijacked host pathways can inhibit viral proliferation in silkworm.…”
Section: Virus-modulated Host Signaling Pathwaysmentioning
confidence: 99%